2018
DOI: 10.12659/msm.910739
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Changes Associated with New Bone Formation Following Osteotome Sinus Floor Elevation (OSFE): A Retrospective Study of 40 Patients with 18-Month Follow-Up

Abstract: BackgroundOsteotome sinus floor elevation (OSFE) is used to increase the bone volume at the site of the maxillary sinus through the transalveolar approach, and may require support with bone grafting. The aim of this retrospective study was to evaluate the radiological changes associated with new bone formation following OSFE during an 18-month follow-up period.Material/MethodsForty patients (including 51 implants) underwent OSFE with final dental reconstruction with a single crown, six months after surgery. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
5
10
0
Order By: Relevance
“…However, Si et al claimed the opposite that the endosinus new bone formation was not significantly correlated with the residual bone height in their 3‐year randomised controlled clinical trial. Yang et al reported also no significant correlation between the new bone formation and the residual bone height. The residual bone height is critical in obtaining initial stability and selecting which programme to operate, but may not directly influenced the amount of new bone formation.…”
Section: Discussionmentioning
confidence: 97%
“…However, Si et al claimed the opposite that the endosinus new bone formation was not significantly correlated with the residual bone height in their 3‐year randomised controlled clinical trial. Yang et al reported also no significant correlation between the new bone formation and the residual bone height. The residual bone height is critical in obtaining initial stability and selecting which programme to operate, but may not directly influenced the amount of new bone formation.…”
Section: Discussionmentioning
confidence: 97%
“…Along the same lines, Yang et al [28] performed a retrospective study on 51 implants by analyzing the radiographic changes found in the first months. They used implants of similar diameter to ours (4.5-5 mm) and with lengths of 6-8 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Several representative parameters are regularly measured in the CBCT images, including residual alveolar bone height, protruded implant length, and total elevated height. The protruded implant length and total elevated height are reported to correlated with the endosinus bone gain in the follow‐ups after bone remodeling and implant osseointegration . For the residual alveolar bone height, studies have demonstrated its impact on the success rate of implant placed in elevated sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Cone beam computed tomography (CBCT) provides comprehensive anatomical information of hard and soft tissues, and has been greatly popularized in dentistry during the last two decades . Nowadays, treatment involving sinus floor elevation regularly employs CBCT scans before surgery to assess the bone volume of the residual ridge, sinus anatomy, the presence or absence of membrane pathological change . Meanwhile, the evaluation of treatment outcomes also involves CBCT scans after the surgery to reconfirm the sinus membrane integrity, implant position, and the dimensions of the augmented volume .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation